Towards the carbon neutrality of sludge treatment and disposal in China: A nationwide analysis based on life cycle assessment and scenario discovery. (April 2023) - Zhou, Xue; Yang, Jixian; Zhao, Xinyue; Dong, Qiyu; Wang, Xiuheng; Wei, Liangliang; Yang, Shan-Shan; Sun, Huihang; Ren, Nan-Qi; Bai, Shunwen
Graphical abstract: Abstract: Motivated by the carbon neutrality target, strategic planning for a low-carbon transition of sludge treatment and disposal in China is challenging due to the unpredictability of technical, regional, socioeconomic, and political factors affecting greenhouse gas (GHG) emissions. This study combines the use of a Life Cycle Assessment and the Patient Rule Induction Method, accounting for possibilities that could achieve net-zero carbon emissions by exploring multiple plausible future profiles of sludge treatment and disposal. Results show that reducing sludge landfill and increasing anaerobic digestion are effective methods to facilitate GHG reduction. Achieving carbon neutrality is closely linked to developing a cleaner electricity mix. Based on a cascaded scenario analysis considering regional differences for 31 Chinese provinces, results demonstrated a maximum cumulative reduction potential of 371 Mt CO2 equivalents from 2020 to 2050, equal to 59.84% of the business-as-usual scenario. Together with GHG reductions, terrestrial acidification and ecotoxicity as well as freshwater ecotoxicity are synergistically reduced. However, the shifting environmental burden results in freshwater eutrophication, human toxicity, marine ecotoxicity, marine eutrophication, and photochemical oxidant formation. This study presents a novel method for systematically identifying possible future development paths toward carbon neutrality. The findings may support policy designs for achieving target carbon reduction effects for sludge disposal.